Single-resistance-controlled quadrature oscillator using current differencing buffered amplifiers - Tangsrirat, W.; Prasertsom, D.; Piyatat, T.; Surakampontorn, W. (My University, 2008)
A single-resistance-controlled quadrature oscillator circuit using current differencing buffered amplifiers (CDBAs) as active components is proposed. The proposed circuit is realised through the employment of two CDBAs, three resistors and two grounded capacitors. Outputs of two sinusoidal with 90 phase difference are available. The oscillation condition and the oscillation frequency of the proposed quadrature oscillator can be controlled independently by a single resistor. In comparison with the previously reported circuits, the proposed configuration considerably reduces the number of passive elements.
Keywords: Current differencing buffered amplifier; Quadrature oscillator; Single-resistance-controlled